An accelerated test stand to assess wear in offshore wind turbines rolling bearings. Issue 2 (April 2018) - Belfiore, Nicola Pio; Costa, Carlo; Pileggi, Rosanna; Botta, Fabio; Guarnaschelli, Claudio
Rolling bearings are universally adopted to serve as revolute joints in almost all mechanisms or machines, because they offer a convenient solution to the problem of minimizing friction and, simultaneously, providing a large load-carrying capacity at any kinematic regime, including slow or alternate rotations. However, in offshore wind turbines not only they reach large dimensions but also they move within strong electromagnetic fields created by the turbine generators. For example, considering the last amplification stadium epicyclic gearbox, they may serve to sustain elements rotating around floating shafts (planetary) which also move around a fixed principal shaft (solar). This article illustrates an original experimental test bench that simulates sliding and rolling contacts through which a test current is flowing. Unexpected and interesting results disclose how this particular field is challenging and how more investigations are still required to achieve an adequate and complete interpretation. The understanding of this phenomenon could give rise to modification to the composition and the microstructure of rollers and rings employed in offshore wind turbines.